2019
DOI: 10.1080/21663831.2019.1702113
|View full text |Cite
|
Sign up to set email alerts
|

Hidden spin-polarized bands in semiconducting 2H-MoTe2

Abstract: We present experimental and theoretical studies of the electronic band structure of 2H-MoTe 2 at high hydrostatic pressures. Photoreflectance measurements allowed the determination of the pressure coefficient of the direct transitions A and B, which are 2.40(3) and −3.42(18) meV/kbar, respectively. We attribute the sign difference to a strong splitting of the conduction bands with increasing pressure and the presence of hidden spin-polarized states in bulk MoTe 2. These results provide direct experimental evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…The presence of such spin-polarized itinerant electrons would imply that these materials are dilute magnetic semiconductors. This idea may be partly supported by the recent report on the observation of hidden spin-polarized states in the bulk MoTe 2 [46]. Although the exact link between µSR and STM/DFT results [9] in 2H-MoTe 2 and 2H-MoSe 2 is not yet clear, both results together constitute a first strong evidence concerning the relevance of magnetic order in the TMDs physics.…”
Section: Summary and Discussionsupporting
confidence: 52%
“…The presence of such spin-polarized itinerant electrons would imply that these materials are dilute magnetic semiconductors. This idea may be partly supported by the recent report on the observation of hidden spin-polarized states in the bulk MoTe 2 [46]. Although the exact link between µSR and STM/DFT results [9] in 2H-MoTe 2 and 2H-MoSe 2 is not yet clear, both results together constitute a first strong evidence concerning the relevance of magnetic order in the TMDs physics.…”
Section: Summary and Discussionsupporting
confidence: 52%
“…These include superconducting phenomena, large quantum efficiencies, large excitonic binding energies, or valley-and spin-degrees of freedom even in their bulk form. [2][3][4] All these exotic properties can be exploited in a wide range of optoelectronic and electronic applications, including transistors, photovoltaics, spintronics or nanoscale light-emitting devices. [5][6][7][8] Despite the associated vast technological interest, TMDs exhibit some fundamental constraints such as limited electron mobilities (below that of silicon) 9 or reduced band gap (typically below 2 eV), 10 which could hinder their implementation in many optoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…Intensive research on 2D materials, such as transition-metal dichalcogenides (TMDs), revealed their remarkable electronic and optical properties. These include strong light-matter coupling [2], large excitonic binding energies, the easiness of producing heterostructures by stacking monolayers held by van der Waals (vdW) forces [3,4], as well as the presence of spin-polarized bands that couple to new degrees of freedom such as degenerate valleys or adjacent layers, even in their bulk form [5,6]. Despite the highly promising properties observed in TMDs for many optoelectronic and spintronic applications, alternative 2D materials with complementary properties are being researched.…”
Section: Introductionmentioning
confidence: 99%